Nanosecond laser pulses for aluminum and copper drilling - Walid K. Hamoudi (Iraqi Journal of Physics, 2018)
Nd:YAG laser pulses of 9 nanosecond pulse duration and operating wavelength at 1.06 μm, were utilized to drill high thermal conductivity and high reflectivity aluminum and copper foils. The results showed a dependence of drilled holes characteristics on laser power density and the number of laser pulses used. Drilled depth of 74 ϻm was obtained in aluminum at 11.036×108 W/cm2 of laser power density. Due to its higher melting point, copper required higher laser power density and/or larger number of laser pulses to melt, and a maximum depth of 25 μm was reached at 13.46×108 W/cm2 using single laser pulse.